Inactivation of the pgmA gene in Streptococcus mutans significantly decreases biofilm-associated antimicrobial tolerance - Nilsson, Martin (2020)
Screening of a Streptococcus mutans mutant library indicated that pgmA mutants displayed a reduced biofilm-associated tolerance toward gentamicin. The biofilms formed by the S. mutanspgmA mutant also displayed decreased tolerance towards linezolid and vancomycin compared to wild-type biofilms. On the contrary, the resistance of planktonic S. mutanspgmA cells to gentamycin, linezolid, and vancomycin was more similar to wild-type levels. Investigations of biofilms grown in microtiter trays and on submerged glass slides showed that pgmA mutants formed roughly the same amount of biofilm as the wild type, indicating that the reduced antimicrobial tolerance of these mutants is not due to diminished biofilm formation. The pgmA gene product is known to be involved in the synthesis of precursors for cell wall components such as teichoic acids and membrane glycolipids. Accordingly, the S. mutanspgmA mutant showed increased sensitivity to Congo Red, indicating that it has impaired cell wall integrity. A changed cell wall composition of the S. mutanspgmA mutant may play a role in the increased sensitivity of S. mutanspgmA biofilms toward antibiotics.